2004
DOI: 10.1046/j.1365-2982.2003.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of resident macrophages from the smooth muscle layers of murine small intestine

Abstract: Macrophages within the murine tunica muscularis were isolated and cultured for physiological studies. Following dispersion, macrophages were identified by phagocytotic activity of fluorescein isothiocyanate (FITC)-dextran. Immediately following isolation, macrophages were rounded and possessed fluorescent granula but developed a ramified shape after 3-4 days in culture. Resident and cultured macrophages were immunopositive for F4/80 and I-Ad/I-Ed. Greater than 90% of F4/80 positive cultured cells were FITC-dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…In the murine bone marrow-derived macrophages, phagocytosable size of latex beads (1.1-µm) stimulated the release of PGE 2 , whereas these macrophages did not respond to nonphagocytosable particles (≥ 40-µm) [24]. In the present study, we demonstrated that the injected FITC-dextran was phagocytosed by muscularis resident macrophages in rat small intestine same as previous reports [15,20,26]. The confocal microscopic study for FITC-dextran uptake and immunohistochemical study based on the results of double staining of dextran and COX-2 protein suggest that FITC-dextran-positive resident macrophages became immunoreactive to COX-2 antibody (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the murine bone marrow-derived macrophages, phagocytosable size of latex beads (1.1-µm) stimulated the release of PGE 2 , whereas these macrophages did not respond to nonphagocytosable particles (≥ 40-µm) [24]. In the present study, we demonstrated that the injected FITC-dextran was phagocytosed by muscularis resident macrophages in rat small intestine same as previous reports [15,20,26]. The confocal microscopic study for FITC-dextran uptake and immunohistochemical study based on the results of double staining of dextran and COX-2 protein suggest that FITC-dextran-positive resident macrophages became immunoreactive to COX-2 antibody (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…concentration: Resident macrophages were isolated from the intestinal muscularis by standard collagenase treatment method as previously described [20]. Freshly isolated macrophages on glass cover slips were loaded with fura-PE3 by exposure to a HEPES buffer solution (in mM: NaCl 125.4, glucose 11.5, KCl 5.9, MgCl 2 1.2, HEPES 10, pH 7.4, either CaCl 2 1.5 or EGTA 0.5) containing 5 µM fura-PE3 acetoxymethyl ester with 0.01% cremophor EL for 30-40 min in a dark room.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…We circumvented this problem by measuring the fractional contribution of Ca 2ϩ to the total ATP-gated membrane current (i.e. the Pf %) using a true-to-life concentration of extracellular Ca 2ϩ and an appropriate membrane potential of Ϫ60 mV (90,91). We found that empirical measurements using recombinant receptors ranged from 3 to ϳ15% by comparison to the average Pf % of the P2X family as a whole (8.6 Ϯ 0.8%; red dotted line of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies specific for this protein label ICC within GI tissues in several species, including humans, and have been widely utilized to both determine ICC cellular morphology, and to characterize sub-populations of ICC located in distinct layers of the muscular wall of the GI tract (Ward and Sanders, 1992;Ward et al, 1994;Burns et al, 1997;Ozaki et al, 2004;Komuro, 1999). Several classes of ICC have been identified.…”
Section: Introductionmentioning
confidence: 99%